Quantum dot doped reduced graphene oxide film and preparation method thereof
By doping graphene quantum dots in reduced graphene oxide films and carrying out P/B/N co-doping and lanthanum loading, combined with aniline tetramer coupling reaction, quantum dot doped reduced graphene oxide films with excellent conductivity and hydrophilicity were prepared, which solved the problems of poor conductivity and insufficient mechanical strength of existing materials, and significantly improved the wet power generation performance and service life.
Patent Information
- Application Number
- CN202510185809.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-20
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2045-02-20
AI Technical Summary
In the existing wet power generation technology, the poor conductivity and strong hydrophilicity of graphene oxide materials lead to limited charge transfer efficiency and insufficient mechanical strength, which limits the wet power generation performance and service life.
By doping graphene quantum dots into reduced graphene oxide films and preparing them by hydrothermal method, phytic acid and 3-aminophenylboric acid are introduced for P/B/N co-doping, and lanthanum elements are supported, and quantum dot dot reduced graphene oxide films with excellent conductivity and hydrophilicity are prepared by coupling reaction between aniline tetramer and modified graphene quantum dots.
It significantly improves the conductivity and mechanical strength of the film, improves the wet power generation performance, extends the service life and storage life, and maintains the stability of long-term operating performance.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite materials, and in particular to a quantum dot-doped reduced graphene oxide film and a preparation method thereof. Background Art
[0002] With the continuous growth of global energy demand and the increasingly serious environmental pollution problem, the development of efficient, clean and sustainable energy conversion and storage technology has become the focus of scientific and industrial circles. Traditional power generation technology mainly relies on the combustion of fossil fuels. Although the technology is mature and widely used, the large amount of greenhouse gases and harmful pollutants released in the process, such as carbon dioxide, carbon monoxide, sulfur dioxide, etc., pose a serious threat to the global climate and ecological environment. Therefore, exploring and developing new renewable energy technologies to replace or reduce dependence on fossil fuels is of vital importance to achieving sustainable development goals.
[0003] Among many new energy technologies, conversion technologies based on waste energy widely existing in the natural environment (such as heat energy, light energy, mechanical energy and water molecule energy) have attracted much attention due to their potential high efficiency and environmental friendliness. In recent years, new power generation methods such as thermoelectric power generation, solar power generation, piezoelectric / friction nanopower generation and salinity gradient power generation have emerged one after another, demonstrating the great potential of converting environmental energy into electrical energy. However, these technologies require specific conditions to generate electricity, such as suitable external climate conditions and mechanical movement, which limits their deployment and potential for sustained power generation. In this context, water-induced power generation technology, as an innovative energy conversion method, has gradually entered the field of vision of researchers because it can utilize the energy difference between gaseous and liquid water molecules that are ubiquitous in nature to achieve efficient generation of electrical energy. In particular, when water molecules interact with the surface of specific nanomaterials, they can trigger a series of physical and chemical processes, thereby driving the movement of charges and generating a potential difference. This process is called hygroelectricity or water-induced power generation. In 2017, Professor Zhou Jun's team first reported a new method to generate electricity using the water evaporation effect on the surface of nanostructured carbon materials, revealing the key role of the interaction between water molecules and carbon layers and evaporation-induced water flow in voltage generation. This discovery not only broadens the boundaries of energy conversion technology, but also provides new ideas for the development of efficient and low-cost hydrodynamic generators.
[0004] Carbon materials, as a type of material with abundant reserves and easy processing on the earth, show good application prospects in the field of hydrothermal power generation due to their unique physical and chemical properties. Among carbon materials, graphene oxide (GO) contains abundant carboxyl groups and has good conductivity. It is the earliest and most widely used material for making hydrothermal generators. Some researchers have reported that they prepared generators by modifying graphene oxide, and used asymmetric oxygen-containing group ion gradients to accelerate the directional transmission of ionic charges, achieving a high power density of 1 mW / cm² and an energy conversion efficiency of up to 52%. However, GO has problems such as poor conductivity, limited charge transfer efficiency due to excessive hydrophilicity, and insufficient mechanical strength during hydrothermal power generation. To solve these problems, researchers proposed a strategy to reduce GO to reduced graphene oxide (RGO). RGO restores the π-π conjugated structure of graphene by removing some oxygen-containing functional groups, thereby significantly improving the conductivity and mechanical strength, and can optimize the hydrophilicity and hydrophobicity of the material by adjusting the degree of reduction to achieve more efficient water molecule adsorption and charge transfer. Furthermore, as a new member of the graphene family, graphene quantum dots (GQDs) have brought new opportunities for hydrothermal power generation technology with their unique quantum effects, high specific surface area and rich oxygen-containing functional groups. GQDs not only inherit the excellent properties of graphene, but also show more outstanding electrical and optical properties due to their small size effect, which makes it possible to improve the performance of hydrothermal generators. Summary of the invention
[0005] The purpose of the present invention is to provide a quantum dot-doped reduced graphene oxide film and a preparation method thereof, which has good hydrophilicity and conductivity, so that the order of the film is improved, the wet-induced power generation performance is improved, and the performance is not attenuated during long-term operation, the service life and storage life are long, and the film has broad application prospects.
[0006] The technical solution of the present invention is achieved in this way: The invention provides a method for preparing a quantum dot-doped reduced graphene oxide film. Citric acid, phytic acid and 3-aminophenylboronic acid are subjected to heating reaction to obtain P / B / N co-doped graphene quantum dots. After lanthanum element is loaded, the surface is modified by a silane coupling agent with an epoxy group, and reacts with an aniline tetramer to obtain a composite. The composite is added into a graphene oxide aqueous dispersion, filtered, immersed in a potassium iodide-hydrochloric acid solution, heated and sealed for reaction, washed, and dried to obtain the quantum dot-doped reduced graphene oxide film.
[0007] As a further improvement of the present invention, the following steps are included: S1. Preparation of P / B / N co-doped graphene quantum dots: citric acid, the first batch of phytic acid, and 3-aminophenylboronic acid were mixed and dissolved in water, heated to react, and then the second batch of phytic acid was added again, heated to react again, dialyzed, and the non-permeated liquid was freeze-dried to obtain P / B / N co-doped graphene quantum dots; S2. Lanthanum loading: lanthanum nitrate was dissolved in water, P / B / N co-doped graphene quantum dots were added, the mixture was stirred and evenly mixed, dialyzed, and the non-permeated solution was freeze-dried to obtain lanthanum loaded P / B / N co-doped graphene quantum dots; S3. Preparation of modified graphene quantum dots: adding lanthanum-loaded P / B / N co-doped graphene quantum dots to water, adding a silane coupling agent with an epoxy group, heating and stirring to react, centrifuging, washing, and drying to obtain modified graphene quantum dots; S4. Preparation of aniline tetramer: dissolving N-phenyl-1,4-phenylenediamine in a mixed solution, adding persulfate, stirring the reaction in an ice bath, filtering, washing with hydrochloric acid, adding ammonia water for dedoping, filtering, washing with ethanol and water in sequence, and drying to obtain aniline tetramer; S5. Preparation of the composite: adding the aniline tetramer and the modified graphene quantum dots to water, stirring the reaction, filtering, washing, and drying to obtain a composite; S6. Preparation of quantum dot-doped graphene oxide film: adding the complex to N,N-dimethylformamide, adding graphene oxide to water, stirring and mixing the two to react, and filtering with a polyvinylidene fluoride filter membrane to obtain a quantum dot-doped graphene oxide film; S7. Preparation of quantum dot-doped reduced graphene oxide film: dissolve potassium iodide in hydrochloric acid, add quantum dot-doped graphene oxide film to soak, heat to seal the reaction, wash, and dry to obtain quantum dot-doped reduced graphene oxide film.
[0008] As a further improvement of the present invention, the mass ratio of citric acid, the first batch of phytic acid, 3-aminophenylboronic acid and the second batch of phytic acid in step S1 is 15-20:2-3:8-10:1-2, the temperature of the heating reaction is 190-210°C, the time is 20-24h, the temperature of the second heating reaction is 190-210°C, the time is 17-20h, and the pore size of the dialysis bag used for dialysis is 3000-4000Da.
[0009] As a further improvement of the present invention, the mass ratio of lanthanum nitrate and P / B / N co-doped graphene quantum dots in step S2 is 0.5-1:10, and the pore size of the dialysis bag used for dialysis is 3000-4000Da.
[0010] As a further improvement of the present invention, the mass ratio of the lanthanum-loaded P / B / N co-doped graphene quantum dots and the silane coupling agent with an epoxy group in step S3 is 10:3-4, the temperature of the heating and stirring reaction is 40-50°C, the time is 2-4h, and the silane coupling agent with an epoxy group is KH560.
[0011] As a further improvement of the present invention, in step S4, the mass ratio of N-phenyl-1,4-phenylenediamine and persulfate is 3-5:4-6, the mixed solution is a mixed solution of 0.1-0.2 mol / L hydrochloric acid and acetone mixed in a volume ratio of 1:0.5-1.5, the stirring reaction time is 3-5 h, the hydrochloric acid concentration used in the hydrochloric acid washing is 0.5-1.5 mol / L, the dedoping time is 10-12 h, and the persulfate is selected from at least one of potassium persulfate, sodium persulfate, and ammonium persulfate.
[0012] As a further improvement of the present invention, the mass ratio of the aniline tetramer to the modified graphene quantum dots in step S5 is 2-3:7-10, and the stirring reaction time is 3-5h.
[0013] As a further improvement of the present invention, in step S6, the mass ratio of the composite to graphene oxide is 7-10:100, and the stirring and mixing reaction time is 1-2 hours.
[0014] As a further improvement of the present invention, the solid-liquid ratio of potassium iodide and hydrochloric acid in step S7 is 4-6 g / 10 mL, the concentration of hydrochloric acid is 0.5-1.5 mol / L, the temperature of the heating and sealing reaction is 90-100° C., and the time is 0.5-1 h.
[0015] The present invention further protects a quantum dot-doped reduced graphene oxide film prepared by the above-mentioned preparation method.
[0016] The present invention has the following beneficial effects: Graphene Quantum Dots (GQDs) have quantum confinement and boundary effects, and show unique properties related to their structure, such as optical, electrical and photoelectric properties. Because of their inherent inertness, they are chemically and physically stable, have a large surface area, abundant active sites, and can promote charge transfer to improve the performance of catalysts through methods such as heteroatom doping, size and morphology regulation, making them have broad application prospects in energy conversion and storage.
[0017] The invention adopts a hydrothermal method to prepare graphene quantum dots. By introducing phytic acid and 3-aminophenylboronic acid, the prepared graphene quantum dots are doped with P, N and B elements. P doping changes the electronic properties of the graphene quantum dots, converts the graphene quantum dots from n-type to p-type semiconductor, increases the number of holes in the graphene, improves the carrier concentration, and thus improves the electrical properties of the graphene quantum dots. N and B doping can cause changes in the energy band and Fermi level of the graphene quantum dots, open the band gap, increase the conductivity of the quantum dots, improve the electron transfer rate of the graphene quantum dots, increase the number of holes, and thus improve the electrical properties, which has a synergistic effect and also improves the hydrophilicity of the prepared film.
[0018] The present invention adopts the method of impregnating lanthanum nitrate salt. Phosphate groups, hydroxyl groups and the like on the surface of carbon quantum dots are helpful for the complexation of lanthanum metal, thereby preparing lanthanum-loaded P / B / N co-doped graphene quantum dots. Lanthanide elements improve the electronic and photoelectronic properties of graphene quantum dots due to their unique 4f electron configuration, thereby improving the power generation conversion and energy storage performance.
[0019] Polyaniline is a conductive polymer, but polyaniline is difficult to dissolve and melt, and difficult to process, which restricts its application prospects. Compared with polyaniline, aniline oligomers have short molecular chains and small molecular weights, and have good solubility, while maintaining the same redox, doping and conductivity as polyaniline. The present invention uses aniline tetramers and modified graphene quantum dots to couple through amino and epoxy reactions to prepare a composite, which is added to a graphene oxide film, and the quantum dots prepared by reduction are doped with the reduced graphene oxide film to improve the conductivity of the film, and the hydrophilicity of the composite film is well improved. At the same time, the composite also improves the order of the film, improves the hydrophilicity of the composite film, and the performance of the hydrophilicity of the composite film is improved. The performance of the hydrophilicity of the composite film is improved, and the performance of the hydrophilicity of the composite film is improved. The performance of the hydrophilicity of the composite film is improved, and the performance of the hydrophilicity of the composite film is not attenuated during long-term operation, and the service life and storage life are long.
[0020] The quantum dot-doped reduced graphene oxide film prepared by the present invention has good hydrophilicity and electrical conductivity, so that the order of the film is improved, the wet-induced power generation performance is improved, and the performance is not attenuated during long-term operation, and the service life and storage life are long, so it has broad application prospects. DETAILED DESCRIPTION
[0021] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] Graphene oxide was purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd. with a purity of >99%, a thickness of <5 nm, an average oxygen content of 35%, and an average sheet diameter of 20 μm.
[0023] Example 1 This embodiment provides a quantum dot doped reduced graphene oxide film, comprising the following steps: S1. Preparation of P / B / N co-doped graphene quantum dots: 15 g of citric acid, 2 g of phytic acid, and 8 g of 3-aminophenylboronic acid were mixed and dissolved in 200 mL of water, heated to 190°C, and reacted for 20 h. Then, 1 g of phytic acid was added again, and the mixture was heated to 190°C again, and reacted for 17 h. The mixture was dialyzed with a 3000 Da dialysis bag for 12 h, and the non-permeated liquid was freeze-dried to obtain P / B / N co-doped graphene quantum dots. S2. Lanthanum loading: 0.5 g of lanthanum nitrate was dissolved in 100 mL of water, 10 g of P / B / N co-doped graphene quantum dots were added, the mixture was stirred for 1 h, dialyzed for 12 h using a 3000 Da dialysis bag, and the non-permeated solution was freeze-dried to obtain lanthanum-loaded P / B / N co-doped graphene quantum dots; S3. Preparation of modified graphene quantum dots: 10 g of lanthanum-loaded P / B / N co-doped graphene quantum dots were added to 200 mL of water, 3 g of silane coupling agent KH560 was added, the mixture was heated to 40° C., stirred for 2 h, centrifuged, washed, and dried to obtain modified graphene quantum dots; S4. Preparation of aniline tetramer: 3 g of N-phenyl-1,4-phenylenediamine was dissolved in 500 mL of the mixed solution, 4 g of sodium persulfate was added, the mixture was stirred in an ice bath for 3 h, filtered, washed with 0.5 mol / L hydrochloric acid, dedoped in ammonia water for 10 h, filtered, washed with ethanol and water, and dried to obtain aniline tetramer; The mixed solution is a mixed solution of 0.1 mol / L hydrochloric acid and acetone in a volume ratio of 1:0.5; S5. Preparation of the composite: 2 g of aniline tetramer and 7 g of modified graphene quantum dots were added to 200 mL of water, stirred for 3 h, filtered, washed, and dried to obtain a composite; S6. Preparation of quantum dot-doped graphene oxide film: 7 mg of the complex was added to 10 mL of N,N-dimethylformamide, 100 mg of graphene oxide was added to 50 mL of water, the mixture was stirred and reacted for 1 h, and the quantum dot-doped graphene oxide film was obtained by filtration with a polyvinylidene fluoride filter membrane; S7. Preparation of quantum dot-doped reduced graphene oxide film: Dissolve 4 g potassium iodide in 10 mL 0.5 mol / L hydrochloric acid, add quantum dot-doped graphene oxide film and soak it, heat to 90°C, seal and react for 0.5 h, wash, and dry to obtain quantum dot-doped reduced graphene oxide film.
[0024] Example 2 This embodiment provides a quantum dot doped reduced graphene oxide film, comprising the following steps: S1. Preparation of P / B / N co-doped graphene quantum dots: 20g of citric acid, 3g of phytic acid, and 10g of 3-aminophenylboronic acid were mixed and dissolved in 200mL of water, heated to 210°C, and reacted for 24h, then 2g of phytic acid was added again, heated to 210°C again, and reacted for 20h, dialyzed with a 4000Da dialysis bag for 12h, and the non-permeated liquid was freeze-dried to obtain P / B / N co-doped graphene quantum dots; S2. Lanthanum loading: 1 g of lanthanum nitrate was dissolved in 100 mL of water, 10 g of P / B / N co-doped graphene quantum dots were added, the mixture was stirred for 1 h, dialyzed with a 4000 Da dialysis bag for 12 h, and the non-permeated solution was freeze-dried to obtain lanthanum-loaded P / B / N co-doped graphene quantum dots; S3. Preparation of modified graphene quantum dots: 10 g of lanthanum-loaded P / B / N co-doped graphene quantum dots were added to 200 mL of water, 4 g of silane coupling agent KH560 was added, the mixture was heated to 50° C., stirred for 4 h, centrifuged, washed, and dried to obtain modified graphene quantum dots; S4. Preparation of aniline tetramer: 5 g of N-phenyl-1,4-phenylenediamine was dissolved in 500 mL of the mixed solution, 6 g of ammonium persulfate was added, the mixture was stirred in an ice bath for 5 h, filtered, washed with 1.5 mol / L hydrochloric acid, dedoped in ammonia water for 12 h, filtered, washed with ethanol and water, and dried to obtain aniline tetramer; The mixed solution is a mixed solution of 0.2 mol / L hydrochloric acid and acetone in a volume ratio of 1:1.5; S5. Preparation of the composite: 3 g of aniline tetramer and 10 g of modified graphene quantum dots were added to 200 mL of water, stirred for 5 h, filtered, washed, and dried to obtain a composite; S6. Preparation of quantum dot-doped graphene oxide film: 10 mg of the complex was added to 10 mL of N,N-dimethylformamide, 100 mg of graphene oxide was added to 50 mL of water, the mixture was stirred and reacted for 2 h, and the quantum dot-doped graphene oxide film was obtained by filtration with a polyvinylidene fluoride filter membrane; S7. Preparation of quantum dot-doped reduced graphene oxide film: Dissolve 6 g of potassium iodide in 10 mL of 1.5 mol / L hydrochloric acid, add the quantum dot-doped reduced graphene oxide film and soak it, heat to 100°C, seal and react for 1 hour, wash, and dry to obtain the quantum dot-doped reduced graphene oxide film.
[0025] Example 3 This embodiment provides a quantum dot doped reduced graphene oxide film, comprising the following steps: S1. Preparation of P / B / N co-doped graphene quantum dots: 17 g of citric acid, 2.5 g of phytic acid, and 9 g of 3-aminophenylboronic acid were mixed and dissolved in 200 mL of water, heated to 200 ° C, and reacted for 22 h, then 1.5 g of phytic acid was added again, heated to 200 ° C again, and reacted for 18 h. The mixture was dialyzed for 12 h using a 3500 Da dialysis bag, and the non-permeated liquid was freeze-dried to obtain P / B / N co-doped graphene quantum dots; S2. Lanthanum loading: 0.7 g of lanthanum nitrate was dissolved in 100 mL of water, 10 g of P / B / N co-doped graphene quantum dots were added, the mixture was stirred for 1 h, dialyzed for 12 h using a 3500 Da dialysis bag, and the non-permeated solution was freeze-dried to obtain lanthanum-loaded P / B / N co-doped graphene quantum dots; S3. Preparation of modified graphene quantum dots: 10 g of lanthanum-loaded P / B / N co-doped graphene quantum dots were added to 200 mL of water, 3.5 g of silane coupling agent KH560 was added, the mixture was heated to 45° C., stirred for reaction for 3 h, centrifuged, washed, and dried to obtain modified graphene quantum dots; S4. Preparation of aniline tetramer: 4 g of N-phenyl-1,4-phenylenediamine was dissolved in 500 mL of the mixed solution, 5 g of potassium persulfate was added, the mixture was stirred in an ice bath for 4 h, filtered, washed with 1 mol / L hydrochloric acid, dedoped in ammonia water for 11 h, filtered, washed with ethanol and water, and dried to obtain aniline tetramer; The mixed solution is a mixed solution of 0.15 mol / L hydrochloric acid and acetone in a volume ratio of 1:1; S5. Preparation of the composite: 2.5 g of aniline tetramer and 8 g of modified graphene quantum dots were added to 200 mL of water, stirred for 4 h, filtered, washed, and dried to obtain a composite; S6. Preparation of quantum dot-doped graphene oxide film: 8 mg of the complex was added to 10 mL of N,N-dimethylformamide, 100 mg of graphene oxide was added to 50 mL of water, the mixture was stirred and reacted for 1.5 h, and the quantum dot-doped graphene oxide film was obtained by filtration with a polyvinylidene fluoride filter membrane; S7. Preparation of quantum dot-doped reduced graphene oxide film: Dissolve 5 g potassium iodide in 10 mL 1 mol / L hydrochloric acid, add quantum dot-doped graphene oxide film and soak it, heat to 95°C, seal and react for 1 hour, wash, and dry to obtain quantum dot-doped reduced graphene oxide film.
[0026] Comparative Example 1 Compared with Example 3, the difference is that phytic acid is not added in step S1.
[0027] The details are as follows: S1. Preparation of B / N co-doped graphene quantum dots: 17 g of citric acid and 9 g of 3-aminophenylboronic acid were dissolved in 200 mL of water, heated to 200°C, reacted for 22 h, dialyzed using a 3500 Da dialysis bag for 12 h, and the non-permeated liquid was freeze-dried to obtain B / N co-doped graphene quantum dots.
[0028] Comparative Example 2 Compared with Example 3, the difference is that step S2 is not performed.
[0029] The details are as follows: S1. Preparation of P / B / N co-doped graphene quantum dots: 17 g of citric acid, 2.5 g of phytic acid, and 9 g of 3-aminophenylboronic acid were mixed and dissolved in 200 mL of water, heated to 200 ° C, and reacted for 22 h, then 1.5 g of phytic acid was added again, heated to 200 ° C again, and reacted for 18 h. The mixture was dialyzed for 12 h using a 3500 Da dialysis bag, and the non-permeated liquid was freeze-dried to obtain P / B / N co-doped graphene quantum dots; S2. Preparation of modified graphene quantum dots: 10 g of P / B / N co-doped graphene quantum dots were added to 200 mL of water, 3.5 g of silane coupling agent KH560 was added, the mixture was heated to 45° C., stirred for reaction for 3 h, centrifuged, washed, and dried to obtain modified graphene quantum dots; S3. Preparation of aniline tetramer: 4 g of N-phenyl-1,4-phenylenediamine was dissolved in 500 mL of the mixed solution, 5 g of potassium persulfate was added, the mixture was stirred in an ice bath for 4 h, filtered, washed with 1 mol / L hydrochloric acid, dedoped in ammonia water for 11 h, filtered, washed with ethanol and water, and dried to obtain aniline tetramer; The mixed solution is a mixed solution of 0.15 mol / L hydrochloric acid and acetone in a volume ratio of 1:1; S4. Preparation of the composite: 2.5 g of aniline tetramer and 8 g of modified graphene quantum dots were added to 200 mL of water, stirred for 4 h, filtered, washed, and dried to obtain a composite; S5. Preparation of quantum dot-doped graphene oxide film: 8 mg of the complex was added to 10 mL of N,N-dimethylformamide, 100 mg of graphene oxide was added to 50 mL of water, the mixture was stirred and reacted for 1.5 h, and the quantum dot-doped graphene oxide film was obtained by filtration with a polyvinylidene fluoride filter membrane; S6. Preparation of quantum dot-doped reduced graphene oxide film: Dissolve 5 g of potassium iodide in 10 mL of 1 mol / L hydrochloric acid, add the quantum dot-doped reduced graphene oxide film and soak it, heat to 95°C, seal and react for 1 hour, wash, and dry to obtain the quantum dot-doped reduced graphene oxide film.
[0030] Comparative Example 3 Compared with Example 3, the difference is that steps S4 and S5 are not performed.
[0031] The details are as follows: S1. Preparation of P / B / N co-doped graphene quantum dots: 17 g of citric acid, 2.5 g of phytic acid, and 9 g of 3-aminophenylboronic acid were mixed and dissolved in 200 mL of water, heated to 200 ° C, and reacted for 22 h, then 1.5 g of phytic acid was added again, heated to 200 ° C again, and reacted for 18 h. The mixture was dialyzed for 12 h using a 3500 Da dialysis bag, and the non-permeated liquid was freeze-dried to obtain P / B / N co-doped graphene quantum dots; S2. Lanthanum loading: 0.7 g of lanthanum nitrate was dissolved in 100 mL of water, 10 g of P / B / N co-doped graphene quantum dots were added, the mixture was stirred for 1 h, dialyzed for 12 h using a 3500 Da dialysis bag, and the non-permeated solution was freeze-dried to obtain lanthanum-loaded P / B / N co-doped graphene quantum dots; S3. Preparation of modified graphene quantum dots: 10 g of lanthanum-loaded P / B / N co-doped graphene quantum dots were added to 200 mL of water, 3.5 g of silane coupling agent KH560 was added, the mixture was heated to 45° C., stirred for reaction for 3 h, centrifuged, washed, and dried to obtain modified graphene quantum dots; S4. Preparation of quantum dot-doped graphene oxide film: 8 mg of modified graphene quantum dots were added to 10 mL of N,N-dimethylformamide, 100 mg of graphene oxide was added to 50 mL of water, the mixture was stirred and reacted for 1.5 h, and the quantum dot-doped graphene oxide film was obtained by filtration with a polyvinylidene fluoride filter membrane; S5. Preparation of quantum dot-doped reduced graphene oxide film: Dissolve 5 g of potassium iodide in 10 mL of 1 mol / L hydrochloric acid, add the quantum dot-doped reduced graphene oxide film and soak it, heat to 95°C, seal and react for 1 hour, wash, and dry to obtain the quantum dot-doped reduced graphene oxide film.
[0032] Comparative Example 4 Compared with Example 3, the difference is that step S3 is not performed.
[0033] The details are as follows: S1. Preparation of P / B / N co-doped graphene quantum dots: 17 g of citric acid, 2.5 g of phytic acid, and 9 g of 3-aminophenylboronic acid were mixed and dissolved in 200 mL of water, heated to 200 ° C, and reacted for 22 h, then 1.5 g of phytic acid was added again, heated to 200 ° C again, and reacted for 18 h. The mixture was dialyzed for 12 h using a 3500 Da dialysis bag, and the non-permeated liquid was freeze-dried to obtain P / B / N co-doped graphene quantum dots; S2. Lanthanum loading: 0.7 g of lanthanum nitrate was dissolved in 100 mL of water, 10 g of P / B / N co-doped graphene quantum dots were added, the mixture was stirred for 1 h, dialyzed for 12 h using a 3500 Da dialysis bag, and the non-permeated solution was freeze-dried to obtain lanthanum-loaded P / B / N co-doped graphene quantum dots; S3. Preparation of aniline tetramer: 4 g of N-phenyl-1,4-phenylenediamine was dissolved in 500 mL of the mixed solution, 5 g of potassium persulfate was added, the mixture was stirred in an ice bath for 4 h, filtered, washed with 1 mol / L hydrochloric acid, dedoped in ammonia water for 11 h, filtered, washed with ethanol and water, and dried to obtain aniline tetramer; The mixed solution is a mixed solution of 0.15 mol / L hydrochloric acid and acetone in a volume ratio of 1:1; S4. Preparation of the composite: 2.5 g of aniline tetramer and 8 g of lanthanum-loaded P / B / N co-doped graphene quantum dots were added to 200 mL of water, stirred for 4 h, filtered, washed, and dried to obtain a composite; S5. Preparation of quantum dot-doped graphene oxide film: 8 mg of the complex was added to 10 mL of N,N-dimethylformamide, 100 mg of graphene oxide was added to 50 mL of water, the mixture was stirred and reacted for 1.5 h, and the quantum dot-doped graphene oxide film was obtained by filtration with a polyvinylidene fluoride filter membrane; S6. Preparation of quantum dot-doped reduced graphene oxide film: Dissolve 5 g of potassium iodide in 10 mL of 1 mol / L hydrochloric acid, add the quantum dot-doped reduced graphene oxide film and soak it, heat to 95°C, seal and react for 1 hour, wash, and dry to obtain the quantum dot-doped reduced graphene oxide film.
[0034] Comparative Example 5 Compared with Example 3, the difference is that 3-aminophenylboronic acid is not added.
[0035] The details are as follows: S1. Preparation of P-doped graphene quantum dots: 2.5 g of phytic acid and 25 g of citric acid were mixed and dissolved in 200 mL of water, heated to 200 ° C, and reacted for 22 h. Then, 1.5 g of phytic acid was added again, heated to 200 ° C again, and reacted for 18 h. The mixture was dialyzed with a 3500 Da dialysis bag for 12 h, and the non-permeated liquid was freeze-dried to obtain P-doped graphene quantum dots.
[0036] Test Example 1 The contact angles of the quantum dot-doped reduced graphene oxide films prepared in Examples 1-3 of the present invention and Comparative Examples 1-5 and the common reduced graphene oxide films without adding the composite were tested on a JC2000D1 (Shanghai, China) instrument. The results are shown in Table 1.
[0037] Table 1
[0038] It can be seen from the above table that the quantum dot-doped reduced graphene oxide films prepared in Examples 1-3 of the present invention have good hydrophilicity.
[0039] Test Example 2 The conductivity of the quantum dot-doped reduced graphene oxide films prepared in Examples 1-3 and Comparative Examples 1-5 was tested using a thermoelectric parameter testing system Namicro-III. The results are shown in Table 2.
[0040] Table 2
[0041] It can be seen from the above table that the quantum dot-doped reduced graphene oxide films prepared in Examples 1-3 of the present invention have higher electrical conductivity.
[0042] Test Example 3 The quantum dot-doped reduced graphene oxide films prepared in Examples 1-3 and Comparative Examples 1-5 were tested, and the moisture-induced power generation performance of GRF-MEG was recorded using Keithley 2000. Short-circuiting treatment was performed before the moisture-induced power generation performance test, and the test environment humidity was controlled by different saturated salt solutions, wherein the saturated solutions were LiCl (13% RH), K2CO3 (43% RH), NaCl (83% RH) and KNO3 (99% RH). The results are shown in Table 3.
[0043] Table 3
[0044] It can be seen from the above table that the quantum dot-doped reduced graphene oxide films prepared in Examples 1-3 of the present invention have good moisture-induced power generation performance.
[0045] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a quantum dot-doped reduced graphene oxide film, characterized in that: P / B / N co-doped graphene quantum dots are prepared by heating citric acid, phytic acid and 3-aminophenylboronic acid, and after loading lanthanum, the surface is modified by a silane coupling agent with an epoxy group, and reacted with aniline tetramer to prepare a composite, which is added to a graphene oxide aqueous dispersion, filtered, immersed in a potassium iodide-hydrochloric acid solution, heated and sealed for reaction, washed, and dried to obtain a quantum dot-doped reduced graphene oxide film.
2. The preparation method according to claim 1, characterized in that: The following steps are involved: S1. Preparation of P / B / N co-doped graphene quantum dots: citric acid, the first batch of phytic acid, and 3-aminophenylboronic acid were mixed and dissolved in water, heated to react, and then the second batch of phytic acid was added again, heated to react again, dialyzed, and the non-permeated liquid was freeze-dried to obtain P / B / N co-doped graphene quantum dots; S2. Lanthanum loading: lanthanum nitrate was dissolved in water, P / B / N co-doped graphene quantum dots were added, the mixture was stirred and evenly mixed, dialyzed, and the non-permeated solution was freeze-dried to obtain lanthanum loaded P / B / N co-doped graphene quantum dots; S3. Preparation of modified graphene quantum dots: adding lanthanum-loaded P / B / N co-doped graphene quantum dots to water, adding a silane coupling agent with an epoxy group, heating and stirring to react, centrifuging, washing, and drying to obtain modified graphene quantum dots; S4. Preparation of aniline tetramer: dissolving N-phenyl-1,4-phenylenediamine in a mixed solution, adding persulfate, stirring the reaction in an ice bath, filtering, washing with hydrochloric acid, adding ammonia water for dedoping, filtering, washing with ethanol and water in sequence, and drying to obtain aniline tetramer; S5. Preparation of the composite: adding the aniline tetramer and the modified graphene quantum dots to water, stirring the reaction, filtering, washing, and drying to obtain a composite; S6. Preparation of quantum dot-doped graphene oxide film: adding the complex to N,N-dimethylformamide, adding graphene oxide to water, stirring and mixing the two to react, and filtering with a polyvinylidene fluoride filter membrane to obtain a quantum dot-doped graphene oxide film; S7. Preparation of quantum dot-doped reduced graphene oxide film: dissolve potassium iodide in hydrochloric acid, add quantum dot-doped graphene oxide film to soak, heat to seal the reaction, wash, and dry to obtain quantum dot-doped reduced graphene oxide film.
3. The preparation method according to claim 2, characterized in that: In step S1, the mass ratio of citric acid, the first batch of phytic acid, 3-aminophenylboronic acid and the second batch of phytic acid is 15-20:2-3:8-10:1-2, the temperature of the heating reaction is 190-210°C, the time is 20-24h, the temperature of the second heating reaction is 190-210°C, the time is 17-20h, and the pore size of the dialysis bag used for dialysis is 3000-4000Da.
4. The preparation method according to claim 2, characterized in that: The mass ratio of lanthanum nitrate and P / B / N co-doped graphene quantum dots in step S2 is 0.5-1:10, and the pore size of the dialysis bag used in the dialysis is 3000-4000Da.
5. The preparation method according to claim 2, characterized in that: In step S3, the mass ratio of the lanthanum-loaded P / B / N co-doped graphene quantum dots to the silane coupling agent with an epoxy group is 10:3-4, the temperature of the heating and stirring reaction is 40-50° C., the time is 2-4 hours, and the silane coupling agent with an epoxy group is KH560.
6. The preparation method according to claim 2, characterized in that: In step S4, the mass ratio of N-phenyl-1,4-phenylenediamine and persulfate is 3-5:4-6, the mixed solution is a mixed solution of 0.1-0.2 mol / L hydrochloric acid and acetone mixed in a volume ratio of 1:0.5-1.5, the stirring reaction time is 3-5h, the hydrochloric acid concentration used in the hydrochloric acid washing is 0.5-1.5 mol / L, the dedoping time is 10-12h, and the persulfate is selected from at least one of potassium persulfate, sodium persulfate, and ammonium persulfate.
7. The preparation method according to claim 2, characterized in that: In step S5, the mass ratio of the aniline tetramer to the modified graphene quantum dots is 2-3:7-10, and the stirring reaction time is 3-5h.
8. The preparation method according to claim 2, characterized in that: In step S6, the mass ratio of the composite to graphene oxide is 7-10:100, and the stirring and mixing reaction time is 1-2 hours.
9. The preparation method according to claim 2, characterized in that: In step S7, the solid-liquid ratio of potassium iodide to hydrochloric acid is 4-6 g / 10 mL, the concentration of hydrochloric acid is 0.5-1.5 mol / L, the temperature of the heating and sealing reaction is 90-100° C., and the time is 0.5-1 h.
10. A quantum dot-doped reduced graphene oxide film prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Green synthetic method for blue fluorescence carbon quantum dots with high fluorescence quantum yield
CN104927849A
Method for preparing graphene quantum dots co-doped with nitrogen, sulfur, phosphorus and chlorine
CN109971470A
Method for synthesizing high-fluorescence boron-nitrogen co-doped graphene quantum dots by one-pot hydrothermal method
CN110922967A
Graphene heating coating and preparation method thereof
CN118772685A
Three dimensional materials quantum dots doped with molecules including hetero atoms and methods of forming the same
KR1020170027612A